2019
DOI: 10.1128/aac.00191-19
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Susceptible OXA-23-Producing Proteus mirabilis in the French Community

Abstract: Nineteen Proteus mirabilis isolates producing the carbapenemase OXA-23 were recovered over a 2-year period in 19 French hospitalized patients, of whom 12 had community onset infections. The isolates exhibited a slightly reduced susceptibility to carbapenems. Whole-genome analysis revealed that all 19 isolates formed a cluster compared to 149 other P. mirabilis isolates. Because of its susceptibility to carbapenems, this clone may be misidentified as a penicillinase producer while it constitutes a reservoir of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In addition, as opposed to other Enterobacterales species, the most prevalent carbapenemases reported in Acinetobacter spp. (i.e., OXA-23, OXA-24/40 and OXA-58) have also been reported in P. mirabilis: OXA-23 in France and Finland, OXA-24/40 in Algeria and OXA-58 in Belgium and Germany (4)(5)(6)(7)(8)(9). Recently, a global phylogenetic analysis has demonstrated that a unique clone of P. mirabilis is responsible for the dissemination OXA-23 or OXA-58 carbapenemases in humans and animals since 1996 (10).…”
mentioning
confidence: 75%
“…In addition, as opposed to other Enterobacterales species, the most prevalent carbapenemases reported in Acinetobacter spp. (i.e., OXA-23, OXA-24/40 and OXA-58) have also been reported in P. mirabilis: OXA-23 in France and Finland, OXA-24/40 in Algeria and OXA-58 in Belgium and Germany (4)(5)(6)(7)(8)(9). Recently, a global phylogenetic analysis has demonstrated that a unique clone of P. mirabilis is responsible for the dissemination OXA-23 or OXA-58 carbapenemases in humans and animals since 1996 (10).…”
mentioning
confidence: 75%
“…In study of Bonnet et al (2002) the bla OXA−23 gene was chromosomeencoded, probably resulting from the integration of a plasmid unable to replicate in Enterobacterales. More recently, Österblad et al (2016) in Finland, andPotron et al (2019) in France also described the occurrence of the bla OXA−23 gene in the chromosome of a P. mirabilis isolate with a close genetic environment typical of A. baumannii with insertion sequences ISAba1, ISAba14 and ISAba125. Other resistance genes would have been inserted together with bla OXA−23 such as sul2, floR, strB, and strA (Österblad et al, 2016).…”
Section: Oxa-23mentioning
confidence: 98%
“…Besides the OXA-48 family, which is exclusively found in Enterobacterales and is thus expected to be found in Proteus, other CHDLs such as OXA-23, OXA-40, OXA-58 that have been exclusively identified in Acinetobacter species (Bonnin et al, 2013a) have recently been identified in P. mirabilis (Bonnet et al, 2002;Girlich et al, 2017;Leulmi et al, 2019;Potron et al, 2019).…”
Section: Oxa-48mentioning
confidence: 99%
“…The frequency of OXA-48 production in the United States has been low, with occasional localized isolates reported (248)(249)(250). Interestingly, OXA-23 is often found in P. mirabilis and was the causative pathogen in a cluster of community-onset infections in France (251). However, this provided only low-level resistance to carbapenems in this organism and may go undetected.…”
Section: Carbapenemase-producing Bacteriamentioning
confidence: 99%